2013
DOI: 10.1163/15685357-01701004
|View full text |Cite
|
Sign up to set email alerts
|

From Homo Faber to Homo Creator? A Theological-Ethical Expedition into the Anthropological Depths of Synthetic Biology

Abstract: Synthetic Biology is supposed to evoke new challenges for science and society. Yet it is a controversial point, up to which extend ethical as well as societal challenges will reach. This paper examines the question as to how a theological-ethical perspective can speak of an anthropological change in the understanding of human beings-as supposed by some philosophers-due to the successes and visions of synthetic biology. Regarding this, the metaphors appearing in the field of synthetic biology (playing God; livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…The data furthermore showed how the linking and embedding of SB mattered more than their ontological status. There were only limited reflections on the rupturing of binary categories such as living and non-living or nature and culture (Braun et al 2013). People focussed more on the processes triggered by and the embedding of synthetic entities as well as its impacts on humans, society and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The data furthermore showed how the linking and embedding of SB mattered more than their ontological status. There were only limited reflections on the rupturing of binary categories such as living and non-living or nature and culture (Braun et al 2013). People focussed more on the processes triggered by and the embedding of synthetic entities as well as its impacts on humans, society and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, phrases with mechanical and industrial references are most prevalent in public discourse on SB in the observed period [ 19 , 20 ]. The empirically observed high usage of metaphorical expressions correspond to the ongoing broad theoretical discussion on metaphors in the field of SB [ 8 , 9 , 21 23 ], which focuses on the occurrence of religiously charged and emotionally appealing expressions, and aims at analysing and assessing SB and its notions of life from a philosophical, ethical or theological perspective.…”
Section: Introductionmentioning
confidence: 86%
“…In the current public discussion, a special focus is put on the visions and (postulated) products of SB, emphasising the objective of generating new forms of life. These future aims, as well as the related successes proclaimed by scientists within this field, show a potential rupture of cultural concepts of life and nature, blurring the classical distinctions between ‘living’ and ‘non-living’ as well as ‘natural’ and ‘artificial’ [ 8 , 9 ]. Such possible developments challenge societal norms and values and may have substantial implications for shared ways of life.…”
Section: Introductionmentioning
confidence: 99%
“…From a religious perspective it is sometimes also assumed that the invention of new forms of life is wrong since it means that we are taking over the role of creator. We are "playing God", so to speak [72][73][74][75]. There is also room for discussion among believers of different religions regarding how to relate to life that is created by us and therefore cannot be conceived of as being created by a god.…”
Section: Practical Implicationsmentioning
confidence: 99%